Transverse colorectal anastomosis in left-sided colorectal stapled anastomosis and risk of anastomotic leak: a single tertiary centre experience - Muthukumarasamy, Navinakathiresu; Ren, Stanley Eng Chee; Henry, Fitzgerald (International Surgery Journal, 2022)
Background: Extensive left colorectal resection following a high IMA ligation can lead to an anastomosis with tension and a compromised perfusion. The aim of this study is to compare the safety and feasibility of transverse colorectal anastomosis in anastomotic leak (AL) following left-sided colorectal stapled anastomosis with a descending colon/ileo – rectal anastomosis. Methods: This retrospective study was performed in a prospectively maintained database at a tertiary colorectal surgical institution in Malaysia to evaluate the impact of performing a transverse colon to rectal anastomosis in a group of patients who underwent left-sided colorectal resection followed by stapled anastomosis from 2019 until 2021. This was compared to another cohort comprising of patients who underwent descending colorectal/ileo-rectal anastomosis. Categorical and dichotomous variables were analysed using chi squared test. Results which were considered significant were if p<0.05. The statistical analysis was performed with IBM Statisticalpackage for social sciences (SPSS) statistics for Mac OS, version25. Results: In that 3 years, 170 patients were included. 77 (45.3%) underwent transverse colorectal anastomosis. The median age of these patients was 58.5. Both groups of patients who underwent transverse colorectal anastomosis and ileo/colorectal anastomosis was homogenous with no significant difference. Our anastomotic leak rate was 8.8% (n=15). 48.8% (n=83) successfully completed their resections laparoscopically. And from our analysis, transverse colorectal anastomosis does not significantly affect anastomotic leak rates (p=0.22) Conclusions: In an experienced tertiary health centre, transverse colorectal anastomosis does not impact anastomotic leak rate and has comparable outcomes to descending colon/ ileo-rectal anastomosis.